Bioaccumulation and Excretion of Enantiomers of Myclobutanil in Tenebrio molitor Larvae Through Dietary Exposure. Issue 12 (7th September 2013) - Lv, Xiaotian; Liu, Chen; Li, Yaobin; Gao, Yongxin; Guo, Baoyuan; Wang, Huili; Li, Jianzhong
ABSTRACT The bioaccumulation and excretion of enantiomers of myclobutanil in Tenebrio molitor larvae through dietary exposure under laboratory conditions were investigated using high‐performance liquid chromatography tandem mass spectrometry (HPLC‐MS/MS) based on a ChiralcelOD‐3R [cellulosetris‐tris‐(3, 5‐dichlorophenyl‐carbamate)] column. The wheat bran fed to Tenebrio molitor larvae was spiked with racemic myclobutanil at two dose levels of 20 mg/kg and 2 mg/kg (dry weight). The results showed that there was a significant trend of enantioselective bioaccumulation in the larvae with a preferential accumulation of (−)‐myclobutanil in 20 mg/kg dose exposure, but it was not obviously observed in the 2 mg/kg dose group. A kinetic model considering enantiomerization between the two enantiomers based on first‐order reactions was built and the rate constants were estimated to discuss the kinetic reason for the different concentrations of individual enantiomers in the larvae. The approximations implied an inversion between the two enantiomers with a relatively higher rate of the inversion from (−)‐myclobutanil to (+)‐myclobutanil. Meanwhile, analysis of data of excretion samples suggested the active excretion is probably an important pathway for the insect to eliminate myclobutanil rapidly with nonenantioselectivity as a passive transport process, which was consistent with the low accumulation efficiency of myclobutanil measured by BAF (bioaccumulation factor). Chirality 25:890–896, 2013. © 2013 Wiley Periodicals, Inc.